Analisis Daya Dukung Tanah Dan Penurunan Pondasi Tiang Pancang Pada Pembangunan Rumah Sakit - Marsal Arija; Zulfhazli Abdullah; Syariaf Asria Nanda; Herman Fithra; David Sarana; Nabila Attarin Ariyono; Ruslan Ruslan (VOCATECH: Vocational Education and Technology Journal, 2026)
AbstractFoundations play a critical role in safely transferring structural loads to supporting soil layers. This study aims to evaluate the axial bearing capacity and settlement of pile foundations under both single-pile and pile-group conditions by comparing the Meyerhof method, the Reese Wright method, and numerical analysis using PLAXIS 2D. The analysis is based on Standard Penetration Test (SPT) data and pile foundation design drawings. The results indicate significant variations among the applied methods. The axial bearing capacity of a single pile is estimated at 441.67 tons using the Meyerhof method, 111.669 tons using the Reese Wright method, and 110.64 tons using PLAXIS 2D. The pile group efficiency is calculated as 0.83 using the Converse–Labarre method and 0.727 using the Los Angeles Group method. Meanwhile, the bearing capacity of pile groups is determined to be 293.40 tons, 74.141 tons, and 167.68 tons using the Meyerhof, Reese Wright, and PLAXIS 2D approaches, respectively. The settlement analysis yields values of 25.3 mm using the Vesic method and 37.7 mm from numerical simulation, both of which are within allowable limits according to SNI standards. These findings indicate that the Reese Wright method provides results closer to numerical analysis, making it more representative for foundation design under similar soil conditions.Keywords:Bearing capacity; Meyerhof method; Plaxis; Pile; Standard penetration test. AbstrakPondasi berfungsi sebagai elemen struktur yang menyalurkan beban bangunan ke tanah pendukung secara aman. Penelitian ini bertujuan untuk mengevaluasi daya dukung aksial dan penurunan pondasi tiang pancang pada kondisi tiang tunggal dan kelompok dengan membandingkan metode Meyerhof, Reese Wright, serta analisis numerik menggunakan PLAXIS 2D. Data yang digunakan berupa hasil Standard Penetration Test (SPT) dan gambar rencana pondasi. Hasil analisis menunjukkan perbedaan yang cukup signifikan antar metode. Daya dukung tiang tunggal diperoleh sebesar 441,67 ton dengan metode Meyerhof, 111,669 ton dengan metode Reese Wright, dan 110,64 ton dari PLAXIS 2D. Efisiensi kelompok tiang sebesar 0,83 dengan metode Converse–Labarre dan 0,727 dengan metode Los Angeles Group. Daya dukung kelompok tiang masing-masing sebesar 293,40 ton, 74,141 ton, dan 167,68 ton untuk metode Meyerhof, Reese Wright, dan PLAXIS 2D. Penurunan pondasi sebesar 25,3 mm (Vesic) dan 37,7 mm (PLAXIS 2D), yang masih memenuhi batas aman SNI. Hasil penelitian menunjukkan bahwa metode Reese Wright memberikan estimasi yang lebih mendekati hasil numerik, sehingga lebih representatif untuk perencanaan pondasi pada kondisi tanah serupa. Kata Kunci: Daya dukung; Metode Meyerhof; Plaxis; Standard penetration test; Tiang pancang.